The city school resource pack understanding the world term 2 nursery (The City School Albakio International Lahore, 2022)
The City School's "Understanding the World" resource pack for kindergarten introduces young learners to their environment, focusing on community, seasons, plants, and animals. It includes engaging, hands-on activities that promote curiosity and exploration. This pack fosters awareness of cultural diversity and encourages social interaction among students.